Innovative dengue vector control interventions in Latin America: what dothey cost? - Sierra, Eduardo Alfonso; Basso, César; Beltrán Ayala, Efraín; MitchellFoster, Kendra; Quintero, Juliana; Cortés, Sebastián; Manrique Saide, Pablo; Guillermo Guillermo, May; Caprara, Andrea; Carvalho de Lima, Edilmar (Inglaterra, 2016)
Background Five studies were conducted in Fortaleza (Brazil), Girardot (Colombia), Machala (Ecuador), Acapulco (Mexico), and Salto (Uruguay) to assess dengue vector control interventions tailored to the context. The studies involved the community explicitly in the implementation, and focused on the most productive breeding places for Aedes aegypti. This article reports the cost analysis of these interventions. Methods We conducted the costing from the perspective of the vector control program. We collected data on quantities and unit costs of the resources used to deliver the interventions. Comparable information was requested for the routine activities. Cost items were classified, analyzed descriptively, and aggregated to calculate total costs, costs per house reached, and incremental costs. Results Cost per house of the interventions were $18.89 (Fortaleza), $21.86 (Girardot), $30.61 (Machala), $39.47 (Acapulco), and $6.98 (Salto). Intervention components that focused mainly on changes to the established vector control programs seem affordable cost savings were identified in Salto (−21%) and the clean patio component in Machala (−12%). An incremental cost of 10% was estimated in Fortaleza. On the other hand, there were also completely new components that would require sizeable financial efforts (installing insecticide-treated nets in Girardot and Acapulco costs $16.97 and $24.96 per house, respectively). Conclusions. The interventions are promising, seem affordable and may improve the cost profile of the established vector control programs. The costs of the new components could be considerable, and should be assessed in relation to the benefits in reduced dengue burden.
Keywords: PATHOGENS AND GLOBAL HEALTH; DENGUE; MANEJO DE VECTORES; CONTROL DE VECTORES